The role of socio-demographic variables and buying habits in determining milk purchasers’ preferences and choices - Merlino, Valentina Maria; Mosca, Oriana; Blanc, Simone; Sparacino, Antonina; Massaglia, Stefano; Borra, Danielle; Mastromonaco, Giulia; Fornara, Ferdinando (Frontiers in Nutrition, 2023)
Emerging new purchasing behaviors have been reflected in the sales trends of dairy products, mainly in cow milk consumption. This study aimed to investigate the preferences of milk purchasers towards different product attributes, by considering both individuals’ socio-demographic characteristics (SD) and milk purchasing habits (PH) as independent variables in the milk consumption model definition. To achieve this objective, a questionnaire was administered to a sample of 1216 residents in the North-West part of Italy. The application of the Best-Worst scaling (BWS) methodology to define the purchasers’ declared preferences towards a set of 12 milk attributes, showed that milk origin and expiry date are the most important attributes for milk choice in the decision making process. The correlation analysis showed that the SD and milk purchasing habits variables affect the definition of stated preferences heterogeneously between the intrinsic, extrinsic and credence attributes.